Phytoconstituent Profiles Associated with Relevant Antioxidant Potential and Variable Nutritive Effects of the Olive, Sweet Almond, and Black Mulberry Gemmotherapy Extracts - Amina Aleya; Emőke Mihok; Bence Pecsenye; Maria Jolji; Attila Kertész; Péter Bársony; Szabolcs Vígh; Zoltán Cziaky; Anna-Beáta Máthé; Ramona Flavia Burtescu; Neli-Kinga Oláh; Andreea-Adriana Neamțu; et al. (MDPI AG, 2023)
The extracts of whole plants or specific organs from different plant species are gaining increasing attention for their phytotherapy applications. Accordingly, we prepared standardized gemmotherapy extracts (GTEs) from young shoots/buds of olive (Olea europaea), sweet almond (Prunus amygdalus), and black mulberry (Morus nigra), and analyzed the corresponding phytonutrient profiles. We identified 42, 103, and 109 phytonutrients in the olive, almond, and black mulberry GTEs, respectively, containing amino acids, vitamins, polyphenols, flavonoids, coumarins, alkaloids, iridoids, carboxylic acids, lignans, terpenoids, and others. In order to assess the physiological effects generated by the GTEs, we developed a translational nutrition model based on Drosophila melanogaster and Cyprinus carpio. The results indicate that GTEs could influence, to a variable extent, viability and ATP synthesis, even though both are dependent on the specific carbohydrate load of the applied diet and the amino acid and polyphenol pools provided by the GTEs. It seems, therefore, likely that the complex chemical composition of the GTEs offers nutritional properties that cannot be separated from the health-promoting mechanisms that ultimately increase viability and survival. Such an approach sets the paves the way for the nutritional genomic descriptions regarding GTE-associated health-promoting effects.